Analysis of methods for determining the stage of sexual maturity in youth sports - Huhka, E. L.; Rudzitis, A. (LASE Journal of Sport Science, 2024)
It is known that at puberty the development of adolescents is very uneven, therefore, their physical abilities are also very diverse, which makes coaches think about the fact that in training groups of the same age, athletes can have different levels of both physical and psychological preparedness. In our opinion, it is very important to find a methodology that can be easily used by coaches to determine the level of puberty of athletes, to optimize the training process for youth athletes. The purpose of this literature review is: 1) to find out and compare different methods for determining the stages of sexual maturity, 2) adapt a method that can be applied in the training process for determining sexual maturity that can be easily practically applied to coaches to create appropriate, individualized training content and methodology for adolescent athletes.